2017
DOI: 10.1002/1878-0261.12075
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein‐related peptidase 4 induces cancer‐associated fibroblast features in prostate‐derived stromal cells

Abstract: The reciprocal communication between cancer cells and their microenvironment is critical in cancer progression. Although involvement of cancer‐associated fibroblasts (CAF) in cancer progression is long established, the molecular mechanisms leading to differentiation of CAFs from normal fibroblasts are poorly understood. Here, we report that kallikrein‐related peptidase‐4 (KLK4) promotes CAF differentiation. KLK4 is highly expressed in prostate epithelial cells of premalignant (prostatic intraepithelial neoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…KLK4 has higher expression in premalignant and malignant prostatic lesions compared to normal prostate epithelia. KLK4 could also increase the expression of VEGF and stimulate human umbilical vein endothelial cells (HUVECs) proliferation [15]. These results indicate that KLK4 might get involved in tumor angiogenesis.…”
mentioning
confidence: 88%
“…KLK4 has higher expression in premalignant and malignant prostatic lesions compared to normal prostate epithelia. KLK4 could also increase the expression of VEGF and stimulate human umbilical vein endothelial cells (HUVECs) proliferation [15]. These results indicate that KLK4 might get involved in tumor angiogenesis.…”
mentioning
confidence: 88%
“…The presence of MFBs has been observed among periacinar fibroblasts adjacent to PIN foci, characterized by increased vimentin staining and α-SMA expression [42]. Furthermore, it has also been demonstrated that prostate epithelial cells in PIN lesions, as well as in malignant lesions, produce kallikrein-related peptidase-4 (KLK4), which induces normal fibroblasts to acquire the CAF phenotype (Figure 1) [99]. In this context, CAFs become more proliferative and start to secrete a series of pro-tumorigenic and pro-angiogenic cytokines, such as IL-8, VEGF, and FGF1 ( Figure 1) [99].…”
Section: The Stroma In Pre-neoplastic Lesionsmentioning
confidence: 99%
“…Furthermore, it has also been demonstrated that prostate epithelial cells in PIN lesions, as well as in malignant lesions, produce kallikrein-related peptidase-4 (KLK4), which induces normal fibroblasts to acquire the CAF phenotype (Figure 1) [99]. In this context, CAFs become more proliferative and start to secrete a series of pro-tumorigenic and pro-angiogenic cytokines, such as IL-8, VEGF, and FGF1 ( Figure 1) [99]. In a mouse genetic model, PI3K alpha catalytic subunit overexpression in prostate epithelial cells led to widespread PIN development with few invasive cells [100].…”
Section: The Stroma In Pre-neoplastic Lesionsmentioning
confidence: 99%
“…However, to date, these functional studies of KLK4 in cancer have been limited to in vitro models. We previously reported that KLK4 induces cancer-associated fibroblast features in prostate-derived stromal cells [5], induces epithelial to mesenchymal transition (EMT)-like characteristics [6], and activates matrix metalloproteinase-1 (MMP-1) [7], which, together, could impact tumor growth and metastasis. Of note, KLK4-transfected PC3 cells had increased migration towards osteoblast-like SaOs2 cell conditioned medium and greater attachment to the bone-matrix proteins, collagens I and IV [8].…”
Section: Introductionmentioning
confidence: 99%
“…For this study, PC3 PCa cells, which do not naturally express KLK4, were selected due to their bone metastasis origin and high aggressiveness, thereby modeling advanced prostate cancer, and importantly, propensity to develop primary tumors and bone metastases in mice, thus providing a model to test our earlier in vitro findings as described above [5][6][7][8]. PCa progression was modeled by injection of PC3 cells, modified to over-express human full length KLK4, in immune-deficient mice via two routes: orthotopically in the prostate to mimic the growth of primary tumors, and intracardiac (left ventricular) to induce metastatic dissemination.…”
Section: Introductionmentioning
confidence: 99%